Construction and psychometric validation in Spanish schoolchildren of a knowledge questionnaire on basic life support and Automated External Defibrillator (ConocES-BLS/AED) in Spain - Belén Gutiérrez-Sánchez; Eva M.ª Montoro-Ramírez; Sebastián Sanz-Martos; Francisco Segura-Galán; Henrique Da Silva Domingues (Resuscitation Plus)
The 60 % of cardiac arrests happen in the out-of-hospital setting. In 2023, the International Liaison Committee on Resuscitation issued a statement entitled “Children save lives”, recommending the teaching of basic life support to children from the age of 12. However, we have not identified validated instruments that assess the level of knowledge of schoolchildren about BLS and AED. Objective: Construction and psychometric validation of a questionnaire to assess knowledge on Basic Life Support (BLS) and Automated External Defibrillator (AED) in primary to secondary school children. Method: Cross-sectional descriptive study of validation of the questionnaire consisting of several phases: construction of the questionnaire on knowledge on BLS and AED (ConocES-BLS/AED), content validation, pilot test and psychometric validation. Results: The ConocES-SVB/AED questionnaire was constructed, content validation was carried out by 14 experts, the pilot test carried out on 105 students reported good reliability (0.84), and finally with the psychometric validation a questionnaire composed of 12 items was obtained and psychometrically validated using the Item Response Theory in a final sample of 182 participants. Adequate fit values and acceptable reliability (0.65) were obtained, demonstrating its usefulness to accurately measure the level of knowledge about SVB/AED maneuvers in schoolchildren. Conclusions: The created and validated questionnaire provides educators with a fundamental resource to identify areas of lack of knowledge, improve and design effective educational interventions for schoolchildren on SVB/AED maneuvers.